2009
DOI: 10.1021/jp9007703
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Pattern Formation in the Copper(II) Oxalate System with Gravity Flow and Axial Symmetry

Abstract: Chemical systems that are far from thermodynamic equilibrium may form complex temporal and spatiotemporal structures. In our paper, we present unusual precipitation patterns that have been observed in the system of Cu(II)-oxalate. Starting with a pellet of copper sulfate immersed in or by pumping copper sulfate solution into a horizontal layer of sodium oxalate solution, we have observed the formation of a precipitate ring and an array of radially oriented thin fingers. The development of these patterns is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 45 publications
1
39
0
9
Order By: Relevance
“…4 While initially the growth of chemical gardens was thought to rely essentially on the chemistry of silica, later studies revealed that also a number of other anions (e.g. aluminate, 5 oxalate, 6 carbonate, 7 phosphate, 8 hydroxide 9 or oxometalate 10 ) can produce similar architectures with a broad range of multivalent metal cations. 1,2,[11][12][13][14] The mechanism for the formation of the typically resulting tubular precipitates was found to be a complex interplay of osmosis, buoyancy and chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…4 While initially the growth of chemical gardens was thought to rely essentially on the chemistry of silica, later studies revealed that also a number of other anions (e.g. aluminate, 5 oxalate, 6 carbonate, 7 phosphate, 8 hydroxide 9 or oxometalate 10 ) can produce similar architectures with a broad range of multivalent metal cations. 1,2,[11][12][13][14] The mechanism for the formation of the typically resulting tubular precipitates was found to be a complex interplay of osmosis, buoyancy and chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, striped patterns have recently been evidenced experimentally in reactive systems when a pellet of copper sulfate is immersed in a sodium oxalate solution. 15 A precipitate in the form of a striped pattern is observed to grow radially. Such stripes also appear when the copper sulfate solution is pumped radially from below into a sodium oxalate solution covered to avoid evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the gravity current carries the more concentrated solution, the precipitate formation depletes the dilute outer electrolyte above. The build-up of carbonate ion by diffusional flux is a substantially slower process, therefore diffusion is insignificant in the precipitate formation [30,13]. In general, these experiments not only demonstrate that transport processes create conditions for selective production of a crystalline form but also may provide insight into natural processes where various gradients play an important role.…”
Section: Discussionmentioning
confidence: 70%
“…These self-organized precipitates have been the subject of several recent studies [6][7][8][9][10], since their controlled synthesis may yield different ordered materials due to the presence of gradients [11,12]. When the precipitate evolves into separate crystalline structures instead of a membrane, the difference in the density of the two electrolytes lead to hydrodynamic instability that results in fluid flow allowing the local mixing of the components [13][14][15]. In this work we construct the latter system and show how morphology can be controlled in the example of calcium carbonate.…”
Section: Introductionmentioning
confidence: 99%